Analisis Pelaksanaan Program Antenatal Care K6 di Puskesmas Banjarsari: Studi Kualitatif - Stephanie, Natasha Griselda; Martha, Evi; Sofyan, Lukman Perdana; Prihastuti, Retno; Isnawati, Isnawati; Hermadi, Hermadi; Siregar, Riski Agussalim (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Introduction: Antenatal Care (ANC) is a health service provided to pregnant woment to reduce the Maternal Mortality Rate (MMR) anf Infant Mortality Rate (IMR). The number of visits K1, K4,and K6 are indicators of service quality. In 2021, Banjarsari Primary Health Care is one of the health centers in Kabupaten Bogor with low K6 value of 26,5%. The objective of this study is to analyze the implementation of the ANC K6 program in the Banjarsari Primary Health Care. Methods: Research with qualitative descriptive method and data collection through in-depth interviews. Results: The number of human resources is sufficient but there are still dual tasks, inadequate facilities and infrastructure such as the narrow building area and a new ultrasound is needed. ANC services use BOK and capitation funds. ANC implementation follows the Renstra Kabupaten Bogor. Conclusions: To increase coverage of ANC K6 in the working area of the Banjarsari Primary Health Care, it is necessary to evaluate the main tasks of human resources, existing facilities and infrastructure, and the implementation process of ANC K6.Keywords: Antenatal care, primary health care, coverage